Globospongicola jiaolongi Jiang, Kou & Li, 2015, a junior subjective synonym of G. spinulatus Komai & Saito, 2006 (Crustacea: Decapoda: Stenopodidea: Spongicolidae) - Wang, Teng-Wei; Komai, Tomoyuki; Chen, Chien-Lin; Chan, Tin-Yam (Zootaxa, 2016)
Morphological and genetic analyses both showed that the abundant material of deep-sea sponge associated Globospongicola shrimps collected off southwestern Taiwan belongs to the same species as G. spinulatus Komai & Saito, 2006 described from the Southwest Pacific and G. jiaolongi Jiang, Kou & Li, 2015 recently described from the South China Sea. Thus, G. jiaolongi is treated as a junior subjective synonym of G. spinulatus. Moreover, it is confirmed that G. spinulatus inhabits general deep-sea area but not in chemosynthetic environment.